Child Marriage Laws around the World: Minimum Marriage Age, Legal Exceptions, and Gender Disparities. (2nd January 2018) - Arthur, Megan; Earle, Alison; Raub, Amy; Vincent, Ilona; Atabay, Efe; Latz, Isabel; Kranz, Gabriella; Nandi, Arijit; Heymann, Jody
ABSTRACT: The marriage of children below 18 is widely recognized in international human rights agreements as a discriminatory global practice that hinders the development and well-being of hundreds of millions of girls. Using a new global policy database, we analyze national legislation regarding minimum marriage age, exceptions permitting marriage at earlier ages, and gender disparities in laws. While our longitudinal data indicate improvements in frequencies of countries with legal provisions that prohibit marriage below the age of 18, important gaps remain in eliminating legal exceptions and gender discrimination.